소형 내장형 시스템을 위한 단일 스택 멀티 스레드 구현 - 김용석(Yong-Seok Kim) (한국컴퓨터정보학회논문지, 2016)
In small embedded systems including IoT devices, memory size is very small and it is important to reduce memory amount for execution of application programs. For multi-threaded applications, stack may consume a large amount of memory because each thread has its own stack of sufficiently large size for worst case. This paper presents an implementation of single stack multi-threading, called SSThread (Single Stack Thread), by sharing a stack for all threads to reduce stack memory size. By using SSThread, multi-threaded applications can be programmed based on normal C language environment and there is no requirement of transporting multi-threading operating systems. It consists of several library functions and various C macro definitions. Even though some functional restrictions in comparison to operating systems supporting complete multi-thread functionalities, it is very useful for small embedded systems with tiny memory size and it is simple to setup programming environment for multi-thread applications. KCI Citation Count: 0